The mediating role of green innovation in the relationship between environmental orientation and firm performance: Evidence from Indonesia - Agustin, Henri; Basuki (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to examine the mediating role of green innovation in the relationship between environmental orientation and firm performance. A sample size of 153 publicly listed companies on the Indonesian Stock Exchange that participated in the PROPER (Public Disclosure Program for Environmental Compliance) program between 2020 and 2023 was chosen, yielding 612 firm-year observations. The Hayes Process macro model version 4 in SPSS 27 was utilized in this study for hypotheses testing. This study found environmental orientation has a positive and significant effect on green innovation. A similar effect was also found on the relationship between green innovation and firm performance. However, the direct effect of environmental orientation on firm performance was insignificant. The results confirmed that green innovation mediates the relationship between environmental orientation and firm performance. The result also reinforces the argument that green innovation plays a key role in improving the performance of business entities in a developing country like Indonesia This study implied that having an environmental orientation encourages firms to be more innovative in creating green processes and products in a variety of ways. It implied that top management should be encouraged to analyze and improve their green innovation practices for maintaining sustainable outperformance from their competitors. The result also implied that policymakers should create an enabling atmosphere to support corporate green innovation. Progressive policies such as subsidies or tax rebates can encourage firms to invest more in green innovation practices.